Extreme immunotherapy: emergency immunology to defeat pandemics - Douglas F. Nixon; Daniela Marín-Hernández; Nathaniel Hupert (BMC, 2021)
Abstract The ongoing global COVID-19 pandemic has thrown into sharp relief the gap between modern biology's ability to investigate and respond to a novel pathogen and modern medicine's ability to marshal effective front-line interventions to limit its immediate health impact. While we have witnessed the rapid development of innovative vaccines against SARS-CoV-2 using novel molecular platforms, these have yet to alter the pandemic's long-term trajectory in all but a handful of high-income countries. Health workers at the clinical front lines have little more in their clinical armamentarium than was available a century ago-chiefly oxygen and steroids-and yet advances in modern immunology and immunotherapeutics suggest an underuse of extant and effective, if unorthodox, therapies, which we now call "Extreme Immunotherapies for Pandemics (EIPs)."